Some Physical-Mechanical Characteristics Of Sesame Plants - Ravshanov Sh; Sherov D; Bozorboev A (Global Scientific Publishing, 2024)
The geometric parameters of the promising sesame variety Tashkent - 112 were studied, as well as the sliding friction angles of its main parts on stainless, steel and plastic surfaces using a special stand. The friction angle values of sesame stalks ranged from 21.60 to 41.80, the lowest values were found in the range from 20.40 to 24.50 on the surface of stainless steel, the difference was 17%. The value of the friction angle decreased by 5.5% during the transition from technological maturation to standard maturation. It has been established that the friction angle of stems located longitudinally in relation to the inclination of the plate is greater than the angle with a transverse arrangement by 5.5% at technological ripeness and by 7.2% at standard ripeness.
Keywords: Mechanization; Sesame; Geometric Properties; Mechanical Properties